Evaluation of mechanical and thermal properties of thermosetting polymer composites - Bansal G.; Kumar Gautam R.; Prakash Misra J.; Kishore C.; Mishra A.; Verma A. (My University, 2025)
Material characterization and optimization has been the first choice of many researchers in the current scenario. Polymer-based composites are the most desired materials among all other materials because of their easy availability, moldability, and customization characteristics. In this chapter, physical, thermal, and mechanical properties of thermoset polymers are discussed in detail. Some examples of thermosetting polymers are bakelite, epoxies, silicones, vulcanized rubber, polyesters, phenolics, polyurethane, nonisocyanate polyurethane, and melamine-formaldehyde polymers. Physical properties of the material include appearance, color, texture, odor, solubility, density, melting point/boiling point, corrosion resistance, resistivity, and magnetism. Mechanical properties of engineering materials include strength, elasticity, plasticity, ductility, malleability, brittleness, stiffness, hardness, creep, fatigue, resilience, toughness, and weldability, and thermal properties of engineering materials include thermal conductivity, specific heat, thermal expansion, thermal resistance, and thermal shock resistance. Comparative analysis is done among different thermoset polymers and the relevant applications are identified. Further, future prospects of thermoset polymer composites are identified for sustainable development. © 2024 Elsevier Inc. All rights reserved.